(untitled) (Polis (Santiago), 2018)
Society is experiencing a series of changes on the relationship between institutions and community. In this context, the university, from its academic mission focused on education and research for the development of knowledge, is promoting greater involvement towards the needs of society, the so-called university’s social responsibility (USR). This article presents how, from a humanistic perspective, a community of social research is established between the Research Unit Person-Centered Approach of the University of Valencia –Spain-, the Research Unit Prisma of the Autonomous University of Bucaramanga –Colombia- and the Albeiro Vargas Foundation (FAVAC) –Colombia- whose purpose is the care of elder. Through a participative research-action methodology, a basis for institutional cooperation for the promotion of psychological well-being of the elderly is created. The volunteering program by the UNAB, through their teachers and students, thus come up with a concrete action of USR whose first activity is the assessment of psychological well-being of the elderly in FAVAC.